Following work design characteristics: Do generations engage differently at work? - Fernandes, Sara; Veloso, Ana; Oliveira , Ana Teresa Ferreira; Silva , Isabel (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Purpose: The effective management of different employees´ generations in the labor market, is important to understand their specific qualities and preferences related to work. This study aims to explore if there are any differences between generations in their engagement towards work and on preferences regarding the social characteristics of work design. Originality/value: Diversity and in particular generational studies is a subject which has been understudied in Portugal and so is their effect on work design, specially on social characteristics. To research and share information that help manage workers from different generations can allow to reach a higher productivity and individual well-being. Design/methodology/approach: Through an online questionnaire, 514 responses were collected from participants belonging to three generations using the shortened version of the Utrecht Work Engagement Scale (UWES-9) by Schaufeli and Bakker (2003), translated and validated for the Portuguese population (Sinval et al., 2018) and a Portuguese translated version of the Work Design Questionnaire (WDQ) (2006) by Morgeson and Humphrey (Proença, 2015), specifically applying the social characteristics items. Findings: Results show statistically significant differences found between generations regarding work engagement and on each of its three dimensions. Considering social characteristics of work design, different needs for feedback were found.